Pengaruh Kepercayaan, Kepuasan Pelanggan, Citra Merek dan Pengalaman Pelanggan Terhadap Loyalitas: Studi Kasus pada Pengguna Iphone - Muhammad Reza Adzaki; Totok Haryanto; Herni Justiana Astuti; Alfato Yusnar Kharismasyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze trust, customer satisfaction, brand image, and experience on the loyalty of iPhone users in Purwokerto. The iPhone product is a smartphone brand produced by Apple, Inc., and is currently very popular with the public because it has an image as a top-notch mobile phone with unique features and appearances that are not owned by other brands. This study is a quantitative study with a sample of 150 respondents selected using purposive sampling techniques. The analysis tool used is multiple linear regression with the help of SPSS Version 25.00 software. The results of the study show that: 1) Trust has a significant positive effect on loyalty, 2) Customer satisfaction does not has a significant positive effect on loyalty, 3) Brand image has a significant positive effect on loyalty, and 4) Experience have a not significant positive effect on loyalty. These results indicate that trust, customer satisfaction, and brand image are important factors in increasing the loyalty of iPhone users in Purwokerto.